2019
DOI: 10.1371/journal.pone.0226377
|View full text |Cite|
|
Sign up to set email alerts
|

Environmental enrichment effects after early stress on behavior and functional brain networks in adult rats

Abstract: Early life stress is associated with long-term and pervasive adverse effects on neuroendocrine development, affecting normal cognitive and emotional development. Experimental manipulations like environmental enrichment (EE) may potentially reverse the effects of early life stress induced by maternal separation (MS) paradigm in rodents. However, the functional brain networks involved in the effects of EE after prolonged exposure to MS have not yet been investigated. In order to evaluate possible changes in brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 96 publications
1
20
0
5
Order By: Relevance
“…In this regard, impaired spatial learning and memory in male rats and deficits in behavioral flexibility in female rats have been associated with hippocampal and prefrontal cortex dysfunction after MS in rodents [ 35 , 37 , 55 ]. However, we found no significant effects of MS on brain CCO activity using a similar MS protocol in our previous study [ 34 ]. This discrepancy with our previous study could be due to multiple comparison errors and the small sample size used, since in this study, only males were analyzed and compared with additional groups reared under environmental enrichment conditions.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…In this regard, impaired spatial learning and memory in male rats and deficits in behavioral flexibility in female rats have been associated with hippocampal and prefrontal cortex dysfunction after MS in rodents [ 35 , 37 , 55 ]. However, we found no significant effects of MS on brain CCO activity using a similar MS protocol in our previous study [ 34 ]. This discrepancy with our previous study could be due to multiple comparison errors and the small sample size used, since in this study, only males were analyzed and compared with additional groups reared under environmental enrichment conditions.…”
Section: Discussionmentioning
confidence: 45%
“…In particular, early MS during the two first weeks of life in rats seems to impair adult HPA axis response, because it overlaps with the ‘stress-hyporesponsive period’ (SHRP, PND 3-14 in rats) characterized by low ACTH and glucocorticoid levels in response to external stressors [ 7 , 32 ]. However, prolonged MS during the entire lactation period (PND 1-21) in rodents may have different effects on the HPA axis function during adulthood, as already reported regarding brain CCO activity [ 34 , 35 ]. Accordingly, increased brain CCO activity in MS female rats as compared to same-sex controls was reported using a short MS period (PND 1-10) that only partially overlapped the SHRP [ 35 ].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Several studies evaluating the effect of EE on brain development have observed increased neurogenesis, increase in dendritic ramifications, as well as increased nerve growth factor (NGF) gene expression and increased LTP in the hippocampus (19)(20)(21). EE has also been shown to improve learning and memory consolidation in animal models of Alzheimer's disease (22,23).…”
Section: Introductionmentioning
confidence: 99%